ГОСУДАРСТВЕННОЕ УПРАВЛЕНИЕ ВОДНЫМИ РЕСУРСАМИ (Journal of actual problems of jurisprudence, 2019)
In given article a state role in realization of norms of a water law in modern conditions has shown that questions of the organization of regulationin the field of water relations are extremely actual for modern development of Republic Kazakhstan. State regulation in the field of water relations onthe importance concerns the basic functions of the state.